Identification of hub genes between moderate to severe asthma and early lung adenocarcinoma through bioinformatics analysis - Jiaqian Xue; Qingwei Zhou (Scientific Reports)
Abstract The objective of this study was to explore the genetic link between moderate to severe asthma and early-stage lung adenocarcinoma (LUAD) using bioinformatic methods. The Cancer Genome Atlas gene-expression profiles for early-stage LUAD and GSE76225 data set for moderate to severe asthma were selected for weighted gene co-expression network analysis, and intersected with the relevant module genes and selected hub genes; the relevant network of hub genes was then determined through a protein–protein interaction network. In addition, gene-set enrichment analysis and gene-set variation analysis (GSVA) were conducted on differentially expressed genes between normal and tumor groups. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway-enrichment analyses were applied to detect hub gene-related biological functions. Receiver operating characteristic (ROC) curves were employed to confirm the diagnostic value of hub genes. We identified four key genes, of which SFTPC exhibited relatively high value for areas under the ROC curves, indicating high diagnostic value for moderate to severe asthma. The clinical efficacy of SFTPC was thus consistent with GSVA results, indicating that moderate to severe asthma can inhibit the occurrence of early LUAD.